2021
DOI: 10.4269/ajtmh.21-0108
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Thalidomide in Patients with Complicated Central Nervous System Tuberculosis: A Systematic Review and Meta-Analysis

Abstract: Thalidomide, an anti-inflammatory and immunomodulatory agent, has a potential role in cases with central nervous system tuberculosis (CNS-TB) with paradoxical reactions. Although several articles have described the use of thalidomide in CNS-TB, no systematic review has been performed in this regard. Different electronic databases were searched for articles describing the use of thalidomide in patients with CNS-TB. For determining pooled estimates in the quantitative review, studies with a minimum sample size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There were no reports of serious adverse events (SAEs) or treatment discontinuation attributable to thalidomide treatment. Peripheral neuropathy was not noted in this study, possibly due to the small sample size and lower dosage of thalidomide compared with the literature [ 5 ]. No matter how, compared with metabolic, osteoarticular, infectious, adrenal, gastrointestinal, ophthalmological, and neuropsychiatric manifestations with prolonged corticosteroid use, the adverse events described in this study seem to be minimal and acceptable [ 12 ].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…There were no reports of serious adverse events (SAEs) or treatment discontinuation attributable to thalidomide treatment. Peripheral neuropathy was not noted in this study, possibly due to the small sample size and lower dosage of thalidomide compared with the literature [ 5 ]. No matter how, compared with metabolic, osteoarticular, infectious, adrenal, gastrointestinal, ophthalmological, and neuropsychiatric manifestations with prolonged corticosteroid use, the adverse events described in this study seem to be minimal and acceptable [ 12 ].…”
Section: Discussionmentioning
confidence: 60%
“…Our analysis included patients with HIV/CM who met the following inclusion criteria: (1) HIV diagnosis was made by a positive western blot HIV antibody test and/or a serum HIV viral load of no less than 5000 copies/mL; (2) CM diagnosis was based on Indian ink staining or culture with the cerebrospinal fluid (CSF); (3) HIV and CM were treated according to the guideline [ 5 ]; (4) patients experienced new or worsening symptoms after antiretroviral therapy (ART) initiation; and (5) culture for Cryptococcus neoformans was negative with the CSF at the time of recurrence. Patients were excluded if they met the following criteria: (1) thalidomide usage since the inductive period of CM; (2) patients who never visited after thalidomide treatment; (3) other etiologies of central nervous system infection; or (4) patients who were already recovering with corticosteroids taper therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, those pleiotropic properties of thalidomide are used as a controversial therapeutic approach to reduce the symptoms of IRIS. In a meta-analysis including 98 children and nine adults, Panda et al had a clinical response rate of 89 % in patients treated with thalidomide for corticosteroids refractory paradoxical reaction related to CNS-TB [ 34 ]. However, a randomized controlled trial conducted by Schoeman et al in children with tuberculous meningitis found no difference in motor outcome between patients who received high dose of thalidomide plus standard-of-care and patients who were treated by placebo in addition to standard-of-care [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study from South Africa showed that thalidomide was safe, well tolerated, and had a modest clinical effect in patients with central nervous system TB-related complications ( Van Toorn et al, 2021b ). However, another review showed that thalidomide had no significant clinical improvement in patients with central nervous system TB compared to the control group and had numerous adverse reactions, while it appeared to be effective in HIV-positive patients with TB-immune reconstitution inflammatory syndrome ( Panda et al, 2021 ). In conclusion, it is important to note that thalidomide can cause severe teratogenic effects and should be used with caution in clinical trials.…”
Section: Repurposed Drugsmentioning
confidence: 99%